THU0095 Difference in Physical Function Between Remission and Low Disease Activity in Early Rheumatoid Arthritis. (9th June 2015) - Galuppi, E.; Farina, I.; Bergossi, F.; De Giorgio, C.; Ciancio, G.; Govoni, M.
Abstract : Background: Remission is the optimal therapeutic goal in treating rheumatoid arthritis to target but low disease activity could constitute a valuable alternative goal especially in patients with long standing disease. Few data exist about the different clinical and functional implications of the two disease activity conditions especially in Early Rheumatoid Arthritis (ERA). Objectives: To investigate whether aiming a state of remission yields some benefit when compared with low disease activity as regard to functional outcomes in an Early Rheumatoid Arthritis cohort of patients. Methods: ERA patients fulfilling 2010 ACR/EULAR who consecutively attended our Early Arthritis Clinic between 2009-2014 were retrospectively analyzed. Patients with available follow-up of at least 1 year were included. Disease activity and functional disability has been evaluated using DAS28 and HAQ after 6 (T6) and 12 (T12) months from diagnosis. Standardized therapeutic approach has been performed according to EULAR guidelines. At T6 and T12 HAQ was compared between patients with different levels of disease activity according to the DAS28: remission (REM-DAS28<2.6) and low disease activity (LDA-DAS28≤3.2). Data were analysed by using t student test. Results: One hundred and thirty-nine patients completed the 1-year follow up. At baseline DAS28 and HAQ were respectively 4.59±1.1 and 0.95±0, 7. At T6 81 (58%) patients achieved DAS28 remission and had an HAQ of 0.27±0.41, 22 (16%) patients were in DAS28 LDA with an HAQ of 0.49±0.5. At T12 83 (60%) patients achieved DAS28 REM and 27 (19%) DAS28 LDA with an HAQ respectively of 0.22±0.35 and 0.75±0.61. At both time points, HAQ resulted significally lower (p<0.05) in REM groups compared to that in LDA. Within the period of observation (from T6 to T12) 11 patients changed from LDA to REM. When investigating the change in physical function in these patients we saw improvement of HAQ from 0.48±0.55 to 0.21±0.29. 13 patients moved from REM to LDA and HAQ deteriorated significantly (REM 0.33±0.3, LDA 0.74±0.49, p =0.01). Conclusions: Even though LDA constitutes an alternative goal especially in patients with long standing disease, our analyses revealed that aiming a state of clinical REM within the first months of the disease, is much better also in term of physical function. Reaching early a good physical function not only will benefit the patient but also will improved major socioeconomic consequences of Rheumatoid Arthritis. References: H Radner, JS Smolen, D Aletaha. Remission in rheumatoid arthritis: benefit over low disease activity in patient-reported outcomes and costs. Arthritis Research & Therapy 2014;16:R56. Disclosure of Interest: None declared